Effects of Corn Silk (Stigma Maydis) Against Blood Glucose Levels of Type 2 Diabetes Mellitus Patients - Alimin, Laurencia (Buletin Farmatera, 2020)
According to WHO, in 2017 there are an estimated 425 million sufferers of diabetes mellitus. Indonesia is placed in the seventh rank in the world in 2015, with an estimated 10 million sufferers. To reduce the prevalence of type 2 diabetes mellitus, improvements need to be made, such as lifestyle modification and treatment. Most anti-diabetic drugs have high side effects. Corn silk is one of the natural ingredients that contain flavonoids, which can reduce blood fat levels. The dose of corn silk of 500 mg/kg BW is the best substance against diabetic rats from excessive weight loss. Therefore, corn silk can be calculated to have an anti-diabetic effect by using lipids, eliminating free radicals, and increasing antioxidant capacity.Â